The Important Double-Edged Role of Astrocytes in Neurovascular Unit After Ischemic Stroke - Han, Guangyuan; Song, Lijuan; Ding, Zhibin; Wang, Qing; Yan, Yuqing; Huang, Jianjun; Ma, Cungen (Frontiers in Aging Neuroscience, 2022)
In recent years, neurovascular unit (NVU) which is composed of neurons, astrocytes (Ast), microglia (MG), vascular cells and extracellular matrix (ECM), has become an attractive field in ischemic stroke. As the important component of NVU, Ast closely interacts with other constituents, which has been playing double-edged sword roles, beneficial or detrimental after ischemic stroke. Based on the pathophysiological changes, we evaluated some strategies for targeting Ast in treating ischemic stroke. The present review is focused on the roles of Ast in NVU and its complex signaling molecular network after ischemic stroke, which may be a prospective approach to the treatment of ischemic diseases in central nervous system.